The Influence of Financial Performance on Stock Prices in Banking Sector Companies Listed on the Indonesian Stock Exchange for the 2019-2021 Period - GOTAMI, Putu Ayu Sabdha; SASTRI, Ida I Dewa Ayu Mas Manik; PUTRA, I Gusti B Ngr. P. (PT Keberlanjutan Strategis Indonesia, 2023)
The research examines the influence of return on assets, debt-to-equity ratio, current ratio, and price-earnings ratio on share prices in banking sector companies listed on the Indonesia Stock Exchange for 2019-2021. This research obtained 36 companies as samples using a purposive sampling technique with three years of observation. he total population of companies is 47, and the sample obtained was 36 companies that met the criteria using the purposive sampling method. The type of data applied is a quantitative approach. The data collected was then analyzed using multiple linear regression. The testing method uses multiple linear regression analysis techniques, classical assumption tests, F-tests, and T-tests. Judging from the results of the partial analysis, it is clear that there is a positive and significant influence of the return on assets and price-earnings ratio variables on stock prices. On the other hand, the debt-to-equity ratio variable and the current ratio variable have a negative and insignificant effect on stock prices.